Highlighting protein fining residues in a model red wine. (1st May 2019) - Maury, Chantal; Sarni-Manchado, Pascale; Cheynier, Veronique
Highlights: Between 24 and 58% of proteins remained in a model wine after fining. Gelatin and hydrolyzed glutens can be labelled by [γ- 32 P] through ATP linkage. Gelatin and hydrolyzed glutens are not precipitated by ethanol. The use of labelled proteins did not modify tannin precipitation. Abstract: Many studies have dealt with fining treatments, focusing on their impact on phenolic precipitation or sensory properties of the treated wines. Previous articles suggested the presence of soluble complexes with tannins and fining proteins, and probably wine polysaccharides too. However, no study has quantified these possible protein residues in wine. The analyses performed on a model red wine to highlight the residual fining proteins were the measurement of viscosity, the quantification of amino acid/proteins of the samples and the radioactivity of the supernatants obtained after fining with a radioactive protein. This work has clearly shown, both qualitatively and quantitatively, the presence of fining residues in a model red wine that had been fined with a gelatin and two hydrolyzed plant proteins. These results have significant implications, yet to be confirmed with commercial fining agents and 'real' wines for allergen residues in treated wines.